1996
DOI: 10.1128/jvi.70.3.1953-1960.1996
|View full text |Cite
|
Sign up to set email alerts
|

Protection against lethal simian immunodeficiency virus SIVsmmPBj14 disease by a recombinant Semliki Forest virus gp160 vaccine and by a gp120 subunit vaccine

Abstract: Infection of pigtail macaques with SIVsmmPBj14, biological clone 3 (SIV-PBj14-bcl3), produces an acute and usually fatal shock-like syndrome 7 to 14 days after infection. We used this simian immunodeficiency virus (SIV) model as a rapid and rigorous challenge to evaluate the efficacy of two SIV Env vaccine strategies. Groups of four pigtail macaques were immunized four times over a 25-week span with either a recombinant Semliki Forest virus expressing the SIV-PBj14 Env gp160 (SFV-SIVgp160) or purified recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(22 citation statements)
references
References 38 publications
0
20
2
Order By: Relevance
“…Previous studies have shown that certain lentivirus-vaccinated hosts, although not fully protected, may nevertheless experience attenuated infections following challenge, as shown by reduced viral loads or delayed disease progression (1,17,18,22,26,31,46). In our study, there was little evidence that the initial p.v.…”
Section: Discussioncontrasting
confidence: 66%
“…Previous studies have shown that certain lentivirus-vaccinated hosts, although not fully protected, may nevertheless experience attenuated infections following challenge, as shown by reduced viral loads or delayed disease progression (1,17,18,22,26,31,46). In our study, there was little evidence that the initial p.v.…”
Section: Discussioncontrasting
confidence: 66%
“…96-well nitrocellulose fi ltration plates (MAHAS45; Millipore) were coated overnight at 4 ° C with the following: 5 μ g/ml each anti -human and anti -human (Rockland); 5 μ g/ml ancestral HIV gp120 ( 31 ); 5 μ g/ml infl uenza vaccine formulation for 2006 -2007 (Sanofi-Pasteur); and 5 μ g/ml keyhole limpet hemocyanin control antigen (EMD Calbiochem). The HIV gp120 protein was produced and purifi ed as previously described ( 32 ). Wells were blocked with RPMI containing 5% FCS for 2 h at room temperature before use.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The cells were allowed to differentiate for a minimum of 8 days prior to use. All envelopes have been expressed and purified as previously described (32,43) and are available through the AIDS Reference and Reagent Program of the Division of AIDS, National Institute of Allergy and Infectious Diseases, National Institutes of Health, Bethesda, Md. (www .aidsreagent.org).…”
Section: Methodsmentioning
confidence: 99%